Management of Islamic Religious Education Learning with a Scientific Approach as a Formation of Active and Scientific Attitudes of Students at SMK Bina Nusantara Andika Cianjur - Ida Nursa'adah; Iana Rotul Halready; Karyana Karyana; Tatang Muh Nasir; Rika Siti Karimah (ISLAMIKA, 2023)
The purpose of this research for demonstrate how the implementation of governance practices, processes, and supporting and inhibiting elements of the scientific method are used to increase student involvement in PAI learning at SMK Bina Nusantara Andika. A qualitative descriptive approach was used in this study. Data collection methods include observation, interviews, and documentation. The findings show that PAI learning is applied using the 2013 curriculum and the scientific model. The school has endeavored to promote discipline and order, maximize study hours using the scientific method, and increase student participation by requiring students to participate in group discussions of the teaching-learning process and hands-on practice. In addition, the instructor demonstrates the scientific method paradigm through real-life examples. The scientific approach is carried out by stimulating students' interest in the concepts being taught, encouraging students to ask questions about concepts, assisting students in gathering various information related to concepts, guiding students in developing arguments from concepts, and guiding students in concluding concepts. In addition, the supporting elements are the active participation of students in learning, competent instructors, supporting facilities and infrastructure, and various learning techniques. On the other hand, the inhibiting factors include inadequate facilities, such as the lack of technical support tools, insufficient allocation of teaching time, and the shortage of teaching staff, especially PAI teachers who have not been able to adapt to the scientific approach model.